Music and social criticism in elementary school music classes (REM. Chilean Journal of Musical Education, 2025)
This work presents an educational proposal created from a project for music classes developed during a supervised internship. Initially, the project was conceived and carried out in remote mode during the social isolation in the year 2021 at the Colégiode Aplicação of the Federal University of Acre with the second year of high school and later reworked and replicated in person with the first-year high school classes in 2022. This methodological proposal addresses social issues through protest songs andtheir significance during the military dictatorship in Brazil in the 1960s and 1970s, as well as in the present day. The objective of this proposal is to place young students in critical-reflexive positions regarding the music they listen to today, as well as tointroduce them to the history of the military dictatorship in Brazil through protest songs. In this process, students are led to observe and understand the musical choices of various Brazilian composers in expressing their social critiques. This work aims to bring socio-historical elements to consciousness through music and compositional processes, strengthening students' critical and reflective sense and developing musical creativity through listening, analysis, and composition. Students are encouraged to listen to and reflect on the military dictatorship through the lens of protest songs and the musical and linguistic strategies used in these songs. They then draw parallels with songs that are part of their own world and contain social critiques. Finally, they propose a group composition that synthesizes the ideas explored, as well as offering a social critique. In developing this project, we sought inspiration from Paulo Freire's critical pedagogy (Freire, 2001; 1987) and theoretical references from creative learning (Odena, 2016; Burnard, 2013; Beineke, 2015).
Keywords: Problem-posing education; Creative learning; Critical thinking; Protest music; Application school